The Influence of Work Environment and Authoritarian Leadership with Work Experience as a Moderating Variable on Job Satisfaction and its Impact on Employee Performance PT. XYZ - Kurniawan, Shelvy; Yolandri, Dea; Andreas, Steven Jose; Gunawan, Farel (Bina Nusantara University, 2024)
This research aims to analyze the impact of work environment and authoritarian leadership towards job satisfaction moderated by work experience and towards employee performance. Questionnaire was used as the data collection technique and distributed using Google Forms to 200 employees of PT. XYZ. The data analysis technique uses SEM-PLS with smartPLS software. The result of this research shows that Work Environment have a significant effect on Job Satisfaction, Work Environment have a significant effect on Employee Performance, Authoritarian Leadership does not have a significant effect on Job Satisfaction, Authoritarian Leadership have a significant effect on Employee Performance, Job Satisfaction have a significant effect on Employee Performance, Work Experience have a significant effect on moderating Work Environment to Job Satisfaction, Work Environment does not have a significant effect on moderating Authoritarian Leadership to Job Satisfaction on PT XYZ.